Phytochemical profiling of Tinospora cordifolia and Convolvulus pluricaulis elucidation against Acetylcholinesterase activity in Neuro-mechanism - M P, Navya Raj; Nataraj Sowmya, Tumakuru; Walmiki, Manasa Ravindra; Chandra S, Jagadeep; kumar B G, Chethan; Kumar K M, Anil; B V, Sushma (Journal of Neonatal Surgery, 2025)
Applications of herbal medicines continues to escalate rapidly upon primary healthcare needs across the population worldwide. Certain natural plant products has been noted be possess therapeutic effects with negligible toxicities endowed with multitude of phytoconstituents responsible for the holistic therapeutic action.in the present study the selected plants were collected dried and extracted using the different solvents and tested for AChE inhibition by Ellman’s method. Further selected extract was evaluated for the phytochemical and quantitative analysis and also antioxidant activity was estimated by DPPH and hydroxyl radical scavenging assay. Cordifolia and C. Pluricaulis on successive extraction hexane yielded the11.4% and 14.7% as highest percentage of extract compared to other solvents. Among all the solvent extracts, ethanol extract of TC and CP showed impressable potency of AChE inhibition in concentration dependent manner in comparison with the other extracts respectively. The results in accordance with the respective standards shown the presence of high content of alkaloid in TPE extract (12.29±0.987) than CPE extract 3.167±0.481) whereas the flavonoid and phenolic contents were found to be more in CPE (26.36±2.030 & 68.67±2.110) extract than TCE extract (16.16±1.097 & 42.11±1.193) respectively. Even the preliminary anti-oxidant activity results in comparison with the standard show the efficiency of both the extract’s potential in anti-oxidation effect with an increase in concentration. Naturally occurring secondary metabolites, polyphenols belong to one of the most well-established classes of bioactive chemicals. Together with a wide range of phytochemicals and enzymes, they make up a substantial store of natural chemical variety. Phytochemical quantification and characterization evidences has a greater need in pharmaceutical health care system in developing nutraceutical formulations against various diseases with lesser adverse effect.